Protected cultivation of vegetables in global arena: A review - SABIR, NAVED; SINGH, BALRAJ (The Indian Journal of Agricultural Sciences, 2013)
Protected cultivation of high value vegetables and cut-flowers has shown tremendous potential during the last decade or so. With the progress of liberalized economy and the advent of newer technologies in agriculture, protected cultivation opens up avenues in agriculture hitherto not seen. These technologies are not only creating avenues at higher level but also to the growers with the smaller landholdings as the higher productivity levels retain economic relevance to agriculture. Protected cultivation is in a way precise, progressive and parallel agriculture encompassing virtually all facets of agriculture and rather under additional scrutiny of technical relevance to situations and grower and market economics. Since protected cultivation is a vast assembly of diverse aspects of agriculture, this review is an effort to bring its current status in global arena covering various components of this important and emerging field of horticulture. Apart from the status, technological components and methodologies, review also discusses principal vegetables like tomato, cucumber, capsicum and lettuce in brief, besides a good amount of treatise on key pests and plant protection strategies in greenhouses.